Comparison of formula‐fed infants with and without colic revealed significant differences in total bacteria, Enterobacteriaceae and faecal ammonia. (15th November 2016) - Savino, Francesco; Quartieri, Andrea; De Marco, Angela; Garro, Maria; Amaretti, Alberto; Raimondi, Stefano; Simone, Marta; Rossi, Maddalena
Abstract: Aim: This study compared the faecal microbial composition of formula‐fed infants who did and did not have colic. Methods: Faecal samples from formula‐fed infants under 16 weeks of age with (n = 38) and without (n = 39) colic were collected at Department of Pediatrics in Turin, Italy, between February 2014 and October 2015. The pH and faecal ammonia were determined and total bacteria, bifidobacteria, lactic acid bacteria and coliforms were quantified by fluorescent in situ hybridisation (FISH). Results: Faecal ammonia was significantly higher in the colicky infants than in the controls (483 vs. 216 μ g/g, p < 0.05). The FISH counts of total bacteria were lower in colicky infants (1.8E10 ± 1.5E10) than in the controls (3.4E10 ± 3.0E10) (p < 0.05). The relative abundance of coliform bacteria was significantly higher in colicky infants (p < 0.05). No differences were observed for the bifidobacteria and lactic acid bacteria counts between the two groups. Conclusion: Our comparison of formula‐fed infants with and without colic revealed significant differences in total bacteria, Enterobacteriaceae and faecal ammonia. This study provides the stimulus for further studies of the gut microbiome, using new methods of analysis such as 16S metagenomics sequencing in order to lead to more tailored dietary approaches. Abstract :